Pengaruh Sistem Informasi Piutang Terhadap Pengendalian Internal Piutang: Studi Pada Salah Satu RSU Di Kota Bandung - Widyatami Regine; Tri Ningsih; Djadjun Juhara; R. Deni Purana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This research aims to know whether there is a significant influence of the accounts receivable system on the internal control of accounts receivable at one of the General Hospitals in Bandung because accounting information systems add value to the organization with accurate, relevant, and timely information. This activity does so that the company's operations become more effective and efficient. Requires internal control as an organizational plan and method for safeguarding assets from fraud and error. The research method used is descriptive and verification methods. The data collection technique distributes questionnaires to 30 employees at one General Hospital in Bandung and processes data using simple linear regression analysis techniques. Based on the research shows that linear regression obtains the equation Y = 3.179 + 0.926X. This result shows that X has a positive and powerful effect on Y. In addition, the accounts receivable system contributes 84% to the internal control of accounts receivable. In comparison, the remaining 16% are other factors not examined. Considering that the accounts receivable system affects the internal control of accounts receivable, the management must further improve the application of the accounts receivable system to create good and more optimal receivables internal control than before.